Ambra1 deficiency impairs mitophagy in skeletal muscle. Issue 4 (20th May 2022) - Gambarotto, Lisa; Metti, Samuele; Chrisam, Martina; Cerqua, Cristina; Sabatelli, Patrizia; Armani, Andrea; Zanon, Carlo; Spizzotin, Marianna; Castagnaro, Silvia; Strappazzon, Flavie; Grumati, Paolo; Cescon, Matilde; et al.
Abstract: Background: Maintaining healthy mitochondria is mandatory for muscle viability and function. An essential surveillance mechanism targeting defective and harmful mitochondria to degradation is the selective form of autophagy called mitophagy. Ambra1 is a multifaceted protein with well‐known autophagic and mitophagic functions. However, the study of its role in adult tissues has been extremely limited due to the embryonic lethality caused by full‐body Ambra1 deficiency. Methods: To establish the role of Ambra1 as a positive regulator of mitophagy, we exploited in vivo overexpression of a mitochondria‐targeted form of Ambra1 in skeletal muscle. To dissect the consequence of Ambra1 inactivation in skeletal muscle, we generated muscle‐specific Ambra1 knockout ( Ambra1 fl/fl : Mlc1f ‐Cre) mice. Mitochondria‐enriched fractions were obtained from muscles of fed and starved animals to investigate the dynamics of the mitophagic flux. Results: Our data show that Ambra1 has a critical role in the mitophagic flux of adult murine skeletal muscle and that its genetic inactivation leads to mitochondria alterations and myofibre remodelling. Ambra1 overexpression in wild‐type muscles is sufficient to enhance mitochondria clearance through the autophagy‐lysosome system. Consistently with this, Ambra1‐deficient muscles display an abnormal accumulation of the mitochondrial marker TOMM20 by +76% ( n = 6–7; P < 0.05), a higher presence of myofibres with swollen mitochondria by +173% ( n = 4; P < 0.05), and an alteration in the maintenance of the mitochondrial membrane potential and a 34% reduction in the mitochondrial respiratory complex I activity ( n = 4; P < 0.05). Lack of Ambra1 in skeletal muscle leads to impaired mitophagic flux, without affecting the bulk autophagic process. This is due to a significantly decreased recruitment of DRP1 ( n = 6–7 mice; P < 0.01) and Parkin ( n = 6–7 mice; P < 0.05) to the mitochondrial compartment, when compared with controls. Ambra1‐deficient muscles also show a marked dysregulation of the endolysosome compartment, as the incidence of myofibres with lysosomal accumulation is 20 times higher than wild‐type muscles ( n = 4; P < 0.05). Histologically, Ambra1‐deficient muscles of both 3‐ and 6‐month‐old animals display a significant decrease of myofibre cross‐sectional area and a 52% reduction in oxidative fibres ( n = 6–7; P < 0.05), thus highlighting a role for Ambra1 in the proper structure and activity of skeletal muscle. Conclusions: Our study indicates that Ambra1 is critical for skeletal muscle mitophagy and for the proper maintenance of functional mitochondria.